z^y sdfhks fskf sfsfhs fskfsf skdf sd

\cos (2\theta) = \cos^2 \theta - \sin^2 \theta

z^y sdfhks fskf sfsfhs fskfsf skdf sd

\cos (2\theta) = \cos^2 \theta - \sin^2 \theta

\left( \begin{array}{c} n \\ r \end{array} \right) = \frac{n!}{r!(n-r)!}

\left( \begin{array}{c} n \\ r \end{array} \right) = \frac{n!}{r!(n-r)!}

\cos (2\theta) = \cos^2 \theta - \sin^2 \theta

http://editorial.discuss.codechef.com/questions/63738/fraud-editroial

added anotyher comment

\left( \begin{array}{c} n \\ r \end{array} \right) = \frac{n!}{r!(n-r)!}

So for answer it is workingâ€¦ but comments mein there is a issue.